Equitable education for migrant students? Investigating the educational success of newly arrived migrants in Flanders - Seynhaeve, Shauny; Vanbuel, Marieke; Kavadias, Dimokritos; Deygers, Bart (Frontiers in Education, 2024)
Previous research has uncovered various inequalities for students in education systems worldwide. In particular, students with a migration background are disadvantaged, but previous research has primarily focused on students with a migration background in general, or native students in general, without examining differences within those groups. This monolithic approach makes it difficult to assess the extent to of differences among students within and across these groups. Using administrative data from the Flemish Department of Education and Training (2009-2019) on 45731 students across 670 schools, this study examines NAMS' passing and dropout rates in Flemish secondary education in comparison to the outcomes of their peers without a (recent) migration background. Data included demographic background variables, educational trajectory variables and indicators of educational outcomes. A crossclassified multilevel regression analysis showed that, after controlling for background variables, NAMS still show higher probabilities of failing a year and of dropping out. Moreover, the impact of SES is stronger for native students than for NAMS. These results provide a comprehensive view of NAMS' educational success by comparing them to diverse groups of mainstream students, and by investigating factors that contribute to these outcomes.